CONVECTIVE MODEL OF THE HEAT FIELD IN THE SURFACE LAYER - Myasnikov V.P.; Ramazanov M.M. (My University, 1989)
In earlier publications the authors developed, within the framework of the hydrodynamic model of the evolution of the Earth, a submodel describing the heat field in the surface layer. They integrated the equation of heat transfer (in the zeroeth approximation) for the model case, and derived certain conclusions about the temperature distribution within the surface layer and about the heat flow through the surface on the basis of this solution. However, only the homogeneous equation was integrated, and the effect of the source was neglected. Now they consider a model of the heat field produced by a radiogenic heat source, which will substantially improve the scenario of previous model. They consider the equilibrium solution and the solution to the unsteady inhomogeneous equation of heat transfer in Lagrangian coordinates, and analyze a specific two-dimensional planar case, in which the strength of the radiogenic source is a stepwise function of depth.